Prospective Validation of Facial Nerve Monitoring to Prevent Nerve Damage During Robotic Drilling - Ansó, Juan; Dür, Cilgia; Apelt, Mareike; Venail, Frederic; Scheidegger, Olivier; Seidel, Kathleen; Rohrbach, Helene; Forterre, Franck; Dettmer, Matthias S.; Zlobec, Inti; Weber, Klaus; Matulic, Marco; et al. (Frontiers in Surgery, 2019)
Facial nerve damage has a detrimental effect on a patient’s life, therefore safety mechanisms to ensure its preservation are essential during lateral skull base surgery. During robotic cochlear implantation a trajectory passing the facial nerve at less than 0.5 mm is needed. Recently a stimulation probe and nerve monitoring approach were developed and introduced clinically, however for patient safety no trajectory was drilled closer than 0.4 mm. Here we assess the performance of the nerve monitoring system at closer distances. In a sheep model 8 trajectories were drilled to test the setup followed by 12 trajectories during which the ENT surgeon relied solely on the nerve monitoring system and aborted the robotic drilling process if intraoperative nerve monitoring alerted of a distance < 0.1 mm. Microcomputed tomography images and histopathology showed prospective use of the technology prevented facial nerve damage. Facial nerve monitoring integrated in a robotic system supports the surgeon’s ability to proactively avoid damage to the facial nerve during robotic drilling in the mastoid.